Trajectory Advances in the Spectrum of Veterinary Oral and Maxillofacial Surgery - Shohreh Ghasemi (New Advances in Medicine and Medical Science Vol. 2, 2023)
Oral diseases are one of the most crucial common diseases in veterinary medicine, but clinical symptoms are usually subtle. In addition, many oral disease in veterinary patients cause significant local and systemic health problems and mostly displays with significant pain in Veterinary patients, however, this is the evident that with the increased demand of medications or treatment for companion animals, with significant treatment for oral diseases. Purpose: The goal of this study is to provide insight into the leading edge of oral and maxillofacial surgery in order to provide a more detailed picture of recent practices and challenges in clinical circumstances that you meet on a daily basis. Methods and Materials: A series of publications containing new information on a wide range of subjects in biomaterials and regenerative research in periodontology, oral surgery, and dentistry, ranging from basic sciences to clinical applications. Results: The findings showed that over the past ten years, numerous studies have concentrated on the molecular, cellular, and pharmacological aspects of the biomaterials utilized to progress oral and maxillofacial surgery. Conclusion: As a result, patients will receive first-rate medical services with less morbidity and treatment. The field of maxillofacial surgery has advanced more. The outcome of surgical treatments depends heavily on preoperative planning, thus academics have concentrated on enhancing it in recent years.